Enhanced Selectivity and Uptake Capacity of CO2 and Toluene Adsorption in Co0.5M0.33MoS4 (M= Sb or Y) Chalcogels by Impregnated Metal Salts. Issue 32 (17th November 2017) - Edhaim, Fatimah; Rothenberger, Alexander
Abstract: The synthesis of metal chalcogenide aerogels Co0.5 M0.33 MoS4 (M= Sb or Y) by the sol‐gel method is reported. In this system, the building blocks [MoS4 ] 2− chelated with Co 2+ and (Sb 3+ ) or (Y 3+ ) salts in nonaqueous solvents forming amorphous networks with a gel property. The chalcogels obtained after supercritical drying have BET surface areas of 176 m 2 g −1 (Co0.5 Sb0.33 MoS4 ) and 145 m 2 g −1 (Co0.5 Y0.33 MoS4 ). Electron microscopy and physisorption studies reveal that the new materials are porous with wide pore size distribution and average pore width of 16 nm. These chalcogels show higher adsorption capacity of toluene vapor (Co0.5 Sb0.33 MoS4 : 387 mg g −1 ) and (Co0.5 Y0.33 MoS4 : 304 mg g −1 ) over cyclohexane vapor and high selectivity of CO2 over CH4 or H2, Co0.5 Sb0.33 MoS4 (CO2 /H2 : 80 and CO2 /CH4 : 21), Co0.5 Y0.33 MoS4 (CO2 /H2 : 27 and CO2 /CH4 : 15). We also demonstrated that the impregnation of various metal species like Li +, Mg 2+, and Ni 2+ significantly enhanced the uptake capacity and selectivity of toluene and CO2 adsorptions in the chacogels. Abstract : Two high surface area chalcogels Co0.5 M0.33 MoS4 (M= Sb, Y) have been synthesized using the sol‐gel metathesis reaction. These materials showed preferential adsorptions of CO2 /(H2 and CH4 ) and toluene vapor. Toluene and CO2 adsorption capacity can be enhanced by post‐synthetic modifications through the addition of different metal species like Li +, Mg 2+, and Ni 2+ . The dispersion of the metal species can create high electric fields on the framework surface leading to high adsorption through Van der Wall forces (electrostatic or quadrupolar interactions).